2020
DOI: 10.1111/iwj.13379
|View full text |Cite
|
Sign up to set email alerts
|

The effect of non‐thermal atmospheric pressure plasma application on wound healing after gingivectomy

Abstract: Recent studies have indicated the potential benefits of Non‐thermal atmospheric pressure plasma (NTAPP) as a novel therapeutic approach. The purpose of the current study was thus to assess the effect of NTAPP on gingival wound healing. Fifteen patients with bilaterally symmetrical gingival hyperplasia were included in the study. After gingivectomy and gingivoplasty, the left‐hand side of the symmetrical surgical area was irradiated with NTAPP (plasma jet kINPen 11). Digital photographs of the gingival wounds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Many studies showed that PBMT was an effective adjunctive treatment that appeared to promote healing following gingivectomy [ 37 39 ]. Besides PBMT, the use of many other topical therapeutic agents have been reported in the literature to improve the wound healing after gingivectomy procedure such as: hyaluronic acid (HA) gel, herbal gel, non-thermal atmospheric pressure plasma application and vitrocure ® gel [ 2 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies showed that PBMT was an effective adjunctive treatment that appeared to promote healing following gingivectomy [ 37 39 ]. Besides PBMT, the use of many other topical therapeutic agents have been reported in the literature to improve the wound healing after gingivectomy procedure such as: hyaluronic acid (HA) gel, herbal gel, non-thermal atmospheric pressure plasma application and vitrocure ® gel [ 2 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gingival wounds of 15 patients after gingivectomy and gingivoplasty were subjected to CAP. The author observed that wound epithelialization was enhanced and wound areas were decreased on the 3rd, 7th, and 14th days after CAP (Kusakci‐Seker & Demirayak‐Akdemir, 2020). In addition, a randomized control clinical trial with 40 patients first evaluated the influence of CAP on postoperative morbidities in the palatal donor area using a free gingival graft (Pekbağrıyanık et al, 2021).…”
Section: Soft Tissue Remodeling Regulated By Cap In Pdmentioning
confidence: 99%
“…Meanwhile, recent clinical studies have demonstrated the benefits of CAP on gingival wound healing (Kusakci‐Seker & Demirayak‐Akdemir, 2020; Pekbağrıyanık et al, 2021). The gingival wounds of 15 patients after gingivectomy and gingivoplasty were subjected to CAP.…”
Section: Soft Tissue Remodeling Regulated By Cap In Pdmentioning
confidence: 99%
“…A gingivectomy operation contributes to periodontal tissue health by removing excess gingival tissues. It improves aesthetics by providing normal physiological contours [ 2 ]. Wound healing after a gingivectomy and gingivoplasty is in the form of secondary wound healing [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The maturation of the connective tissue occurs in 7 weeks [ 1 , 4 ]. Various products, such as low-dose laser applications, herbal products, hemostatic agents, ozone, antiseptic/antibacterial agents with bioactive material, and platelet concentrates, have been tested to accelerate wound healing after a gingivectomy and gingivoplasty [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%